การพัฒนาต้นแบบการให้บริการนวดตามหลักคัมภีร์พระไตรปิฎก เพื่อสร้างเสริมลักษณะการผ่อนคลาย : การศึกษาเชิงพฤติกรรม - คำธร วีรชัย; ขัตติยะ ภุมรินทร์; เอกภัทร อภิฉนฺโท (วารสารวิจัยราชภัฏธนบุรี รับใช้สังคม, 2024)
Thai massage is a type of traditional therapy based on the principles of the Tripitaka scriptures which are part of Thai culture. Along with health care, it has been used to promote healthy behavior. According to modern medical science this study aims to study the mechanisms of brain function. This research aims to examine the mechanisms underlying brain function, and characteristics of behavioral relaxation. It focuses on comparing foot and shoulder massage techniques that influence relaxing qualities. Additionally, to support the Tripitaka’s scriptures’ massage model for encouraging relaxation. This study employed a hybrid methodology that combined quantitative and qualitative techniques. Data were collected using questionnaires and interviews with a reliability score of 0.978 by providing participants with self-evaluation surveys. Semi-structured interviews were employed for the interviews. Both content data and statistical data need to be analyzed. Utilizing fundamental statistics such as quantity, percentage, mean, and standard deviation. The important results were as follows: (1) overall relaxed nature is the highest level (mean = 4.71). While comparing the highest to lowest average; Item 6 Service recipients believe that foot massage is good and beneficial, especially in creating a feeling of relaxation (mean = 4.80); Item 1 Believes that the feeling of relaxation in both the body and mind (mean = 4.77); Item 10 Massage with wisdom should be widely disseminated to create a feeling of relaxation among the people (mean = 4.73), respectively. (2) Characteristics of behavioral relaxation were found that users of foot massages were more relaxed than users of shoulder massages, it was believed that massage helps increase blood circulation throughout the body, foot massage method (mean = 4.58); shoulder massage method (mean = 4.38). (3) Both foot massage and shoulder massage were effective at improving the body’s circulation as a form of massage that can induce relaxed. Massage influenced a sense of calm and was connected to the brain’s systems and functions. Therefore, Thai massage is a complementary medical procedure for promoting physical and mental calm. It is a method of treatment based on the principles of Buddhist scriptures, Thai traditional medicine, and medical science.